Does the introduction of IFRS change the timeless of loss recognition? Evidence from German firms - Sebastian Brauer; Carl-Friedrich Leuschner; Frank Westermann (Osnabrück University, Institute of Empirical Economic Research, 2011)
In this paper, we re-evaluate the hypothesis that the introduction of the IFRS has an impact on the timeliness of loss recognition. We test this hypothesis in a data set of public German firms that report according to German-GAAP and IFRS, respectively. The parallel use of the two accounting standards in Germany provides a unique opportunity to contribute to the academic discussion, as well as to the current policy debate on regulatory reform in Germany. Starting from the standard time series concept of conditional conservatism that was initially proposed by Basu (1997), we implement a wide range of test specifications, including (i) a threshold unitroot test specification; (ii) a multivariate approach to outlier detection and (iii) various forms of controlling for fixed effects. We do not find evidence that IFRS and German-GAAP firms differ with respect to their timeliness of loss recognition in any of these specifications - a result that appears surprising in light of the more prudent regulation in the German-GAAP, but is consistent with some earlier findings in the literature.
Keywords: M41; M48; C22; K22; 330; IFRS; German-GAAP; Timely loss recognition; Conservatism